Pengembangan Sediaan Serbuk Antidiabetes dari Kombinasi Ekstrak Kulit Buah Manggis (Garcinia Mangostana L.) dan Ekstrak Daun Salam (Syzygium polyanthum (Wight) Walp.) - Rizki Yulianti; Partomuan Simanjuntak; Anny Victor Purba (Faculty of Pharmacy, Universitas Muslim Indonesia, 2020)
Diabetes mellitus is a metabolic disease characterized by hyperglicemic. Mangosteen (Garcinia mangostana L.) and Salam (Syzygium polyanthum (Wight) Walp.) are plants which recognized as blood glucose controller. The study aims to determine the effectiveness of the combination of the two extract in decreasing blood sugar levels of diabetic rats. The rats divided into 6 groups: group I (normal control) without treatment, group II (negative control), group III (positive control), group IV (extract of mangosteen with dose of 400 mg), group V (extract of salam leaf with dose of 400 mg) and group VI (combination of mangosteen 200 mg and salam leaf 200 mg). Data were analyzed by One-Way Anova, followed by PostHoc Bonferroni analysis. Then the combination of the extract was formulated in powder dosage form blended with PVP, Sucralose and Lactose. The evaluation included physical test are organoleptic, water content and flowability time. The results showed that the combination of the extracts of mangosteen and salam leaf comprising half doses of eact extract could lower blood glucose levels significantly (P<0.05) with better efficacy than each single extract and the combination of extracts able to produce powder dosage form with the requirement (organoleptic, water content and flowability time).